Quality Analysis of Different Brands of Captopril Table (Revista Brasileira Multidisciplinar, 2014)
Quality control consists of a set of operations in order to verify if the product conforms to the specifications of the pharmacopoeia, to assure its safety, its therapeutic efficacy and its quality, throughout the validity period. For the patient, the lack of quality of the product causes serious trouble with health risks. The annual consumption of antihypertensive drugs rose from January 2010 to April 2013, an increase of 41.1 million to 119 million units, with 16.57% share of sales attributable to drugs to control blood pressure in which captopril represents 1.47%. Considering these data, the present study aimed at quantifying the content of captopril tablets of different brands available in the pharmaceutical market. Analyses were performed with 25 mg tablets of six different laboratories, being three similar and three generic ones. The analysis methodology was based on titrimetric method, determining the individual and mean weight of the tablets analyzed, as shown in the official methodology. Duplicate analyzes were performed. The data were statistically evaluated by determining the coefficient of variation and standard deviation. Despite the analyzed brands present statistical differences, it is possible to confirm that the tests of all samples were within the established standards.
Keywords: Quality Control; Analysis; Captopril.